Social Impact of Converting Rice Field Agricultural Land into Housing - Yuniati, Ati; Hamidah, Upik; Nurmayani, Nurmayani; Deviani, Eka (Unifikasi : Jurnal Ilmu Hukum, 2024)
Land conversion refers to the shift in the use or function of land, which has become increasingly common due to population growth and the rising demand for housing, food, and infrastructure. In Pesawaran Regency, particularly in Mada Jaya Village, the conversion of rice fields into housing presents both procedural challenges and significant social impacts. This study examines the process of land conversion and its social consequences, focusing on two key questions: how the conversion process is carried out and what social impacts arise from it. This study applies Talcott Parsons' functional structural theory using the AGIL framework, supported by legal analysis and field studies, to offer practical insights into sustainable land management. The findings reveal that while land conversion should follow legal procedures, such as obtaining a location permit and land use transfer permits, discrepancies occur in practice. Some agricultural land has been pre-filled with soil, classifying it as productive land and making it ineligible for conversion permits. The social impacts include reduced food availability, unemployment, and economic instability, despite some landowners benefiting from land sales. To address these challenges, stricter enforcement of regulations, community participation, and support programs for displaced workers are needed. Economic diversification, such as small business development and agro-tourism, is also recommended.